24. PERCEPTION OF FACIAL AESTHETICS IN STANDARDIZED PHOTOS AMONG STUDENTS OF HANOI NATIONAL UNIVERSITY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Faces play an important role in human social interactions. An unaesthetic face canaffect people's physical, mental, psychosocial and emotional health, causing them to lose theirconfidence.Objective: Describe the current status of face perception on standardized images in students of HanoiNational University in 2023.Method: Cross-sectional descriptive study conducted on 259 students.Results: Short, straight male faces and straight, average female faces have the highest average scoresof 8.25 and 8.61; Long, concave male and female face types have the lowest average scores of 2.09and 2.52.Conclusion: Short, straight male faces and straight, average female faces are the most beautiful,concave, long male and female faces are the worst. There is no significant difference in the perceptionof beauty of facial types between student groups.
Keywords: Perception, Facial profile, Aesthetics, Treatment necessity.